EFEKTIVITAS PROMOSI DALAM MENINGKATKAN JUMLAH WISATAWAN DI GRAND PURI WATER PARK YOGYAKARTA - , KHAIRI AMALINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to determine the effectiveness of Promotion strategy of Grand Puri Water Park Yogyakarta In Increasing Number of Travelers in Grand Puri Water Park Yogyakarta. This study implemented by using data collection methods of observation, interviews, questionnaires, documents and documentation. The number of questionnaire respondents were conducted. in this study, data collection is 62 travelers. The questionnaire will be used in this study is closed-type questionnaire .with answers that have been prepared, so that the respondent is only allowed to select total of 11 questions. Descriptive analysis technique used with a frequency distribution table to explain the characteristics of the respondents. Which will then be reviewed and analyzed using a comparison between the results of the questionnaire, the number of tourists, tourist targets, and promotion budgets between 2013 and 2014. This study shows that: the overall promotion conducted by the Grand Puri Water Park Yogyakarta is already Effective in communication (Information Dissemination), as well as a target (n umber of visits), it can be seen from promotional activities of Yogyakarta Grand Puri Water Park in 2014 by lowering 11.5% when compared to the budget of the year 2013. annual visits with a target reduction of 1%. In 2013 the number of visits in January to May successfully accounted for 35.20% of the annual target in 2013, in 2014 the number of visits in January to May successfully accounted for 41.35%, up 6.15% from last year.